The Christmas Miracle of Jonathan Toomey - Wojciechowski, Susan; Illustrated by Lynch, P.J. (London Candlewick Press, 1995)
The widow McDowell and her seven-year-old son Thomas ask the gruff Jonathan Toomey, the best wood-carver in the valley, to carve the figures for a Christmas crib.
Include Color Illustration
Keywords: Christmas stories -- Wood-carving -- Bereavement